PENERAPAN PROSEDUR VOUCHING DALAM AUDIT ATAS AKUN PIUTANG: STUDI PADA PT. XYZ OLEH KAP X - Abkoria, Trimita; Islamudin, Ardhi (Program Studi Akuntansi Universitas Flores, 2026)
This study analyzes the application of Vouching procedures in auditing accounts receivable, especially in the context of assignments carried out by the Public Accounting Firm (KAP) X to the client entity PT. XYZ. This research was conducted using a case study method and a qualitative approach. In the qualitative approach, data were obtained through interviews using flexible but focused guidelines, with an auditor at KAP X who has direct experience in handling the Vouching process for accounts receivable. The results of this study reveal that the implementation of Vouching for accounts receivable at PT. XYZ requires more than just collecting evidence and the involvement of only one informant limits the perspective of this study. The implication is that Vouching needs to be seen as a strategic process and further research should involve more informants.